Leading higher education as and for the public good - Roxå, Torgny (Högre utbildning, 2020)
Review of: Leading higher education as and for public good: Rekindling education as praxis. Edited by Tone Dyrdal Solbrekke & Ciaran Sugrue, London, Routledge, 2019, 180 pp., £ 34.99 (paperback), ISBN 978-0367205126